The disclosure of materiality in the non-financial: reporting of listed European entities - Gomes, Miguel (2024)
Materiality is a crucial concept in accounting and auditing, allowing relevant matters to be determined from the perspective of the entity and its stakeholders. With the issuance of recent European Directives on sustainability, new issues have been emerging in regard to what concerns its definition and scope within the entities’ non financial information (NFI) reporting. This exploratory study addresses, through the lens of institutional theory, an objective linked to disclosures about materiality in NFI reporting, assessing this information with a breakdown by industry and country. The study adopts archival research as a method and content analysis as an investigation technique, using as a source different consolidated NFI reports (reports and accounts, sustainability, and integrated reports) relating to the year 2021 from the entities that make up the main indices of Euronext countries. Overall, the findings do not show a high disclosure level on the issues related to materiality, which means that a reduced level of transparency was found in the European entities’ NFI reporting. Moreover, the findings do not support significant differences by country and industry. The study is pertinent in the context of the discussion about the content of disclosure of materiality in the NFI report. In addition, it assumes particular importance due to the diversity of topics addressed related to materiality in NFI reporting, making it relevant for standardization bodies, regulators, auditors, and different stakeholders of NFI reporting. As far as the authors are concerned, this is the first research that assesses the disclosure of materiality in NFI reporting, covering multiple European countries and industries.